Optimization of the cost of extraction of vegetable oils in the environment of family agriculture in mato grosso - Bueno, Adauto Farias; Piasson, Diego [UNESP]; Gauto, Ruben Francisco (My University, 2018)
The present study applies the algorithm of the Johnson and Montgomery (1974) as rotational cycle policy (Fernandes and Godinho Filho, 2010) for a problem of sequencing and dimensioning of batch of raw multi-raw material oils (single stage) with process of extraction in a family farming environment. Specifically, the research employs the modeling and simulation procedure to derive the minimum total cost of the process. It is also used the documentary research procedure to generate a profile of family agriculture as a supply agent in the Brazilian biodiesel chain and determination of the parameters of the model. The results were obtained through the software Wolfram Mathematica 10.1 and present a scenario of great difficulties for family agriculture in the supply chain of biodiesel, but at the same time opportunities in higher value-added chains, such as comestics and pharmaceuticals. Minimization of total annual incremental cost (CITA) was obtained under the production of two batch sequences of four types of oils, in one year.
Keywords: Biodiesel; Costs; Family farms; Oils; Supplies